"מה זה הדבר הזה שזוהר כל הזמן שאני מסתירה" : על ראנא של חדוה הרכבי - אדף, שמעון (מכאן, 2016)
In her poetry collection Rana, Hedva Harechavi creates a new form of poetical expression by inquiring into the basic elements of fiction writing: narrative, characters and the workings of the signifying mechanism. She does not put the elements to use in the poems, nor does she discard them. However, by relentlessly deconstructing and reconstructing them in an effort to devise her means of dealing with loss, Harechavi poses a deeper question about the role of ‘that which cannot be thought’ in poetry.